The role of network structure in integrated water management: a case study of collaboration and influence for adopting nature-based solutions - Castro, Cyndi Vail; Carney, Clint; de Brito, Mariana Madruga (Frontiers in Water, 2023)
Integrated water management functions beyond traditional hydrology by considering the intricate dynamics of social impacts, environmental health, and ecosystem services in the management of water resources. Such dynamics are best elucidated when diverse stakeholder types are included in the decision-making process. However, stakeholders from differing backgrounds may disagree upon best practices and collective paths forward. Here, we demonstrate how network structure impacts collaboration and influence within integrated water management. Using network analysis, we examine the arrangement of connections (i.e., network topology) between multifaceted elements (e.g., social challenges, exogenous factors, management opportunities) in an integrated water management system. The rationale for using network analysis within integrated water management is that we cannot impact the decision-making process without first understanding the context within which effective governance can take place. By analyzing topological patterns within the management system, we can identify the extent to which key governance principles (e.g., information flow, collective decision-making, power relations) are manifested and aid in transitioning the system toward effective change. Specifically, we explore a case study regarding how decision-making stakeholders from various sectors and levels of governance in Houston, Texas, USA engaged in fuzzy cognitive mapping to define a management system for improving the uptake of nature-based solutions. We compute several network statistics (e.g., density index, hierarchy index, centrality index) to explore the topology of the integrated water management system. Our findings highlight collaborative opportunities embedded within the management system, which, when mobilized, could have varying degrees of influence on policy initiatives. Through this lens, we explore how the network structure is associated with complex decision-making across socio-institutional scales. We compare these insights with stakeholder beliefs about the management system. We conclude with recommendations for leveraging network analytics in integrated water management to better understand topological relationships among stakeholders and the systems they seek to shape.